2013
DOI: 10.1016/j.jlumin.2012.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Bi3+–Ce3+ energy transfer and luminescent properties of LuAG:Bi,Ce and YAG:Bi,Ce single crystalline films

Abstract: The absorption, cathodoluminescence, excitation spectra of photoluminescence (PL) and PL decay kinetics were studied at 300 K for the double Bi3+-Ce3+ doped and separately Bi3+ and Ce3+ doped Y3Al5O12 (YAG) and Lu3Al5O12 (LuAG) single crystalline film phosphors grown by liquid phase epitaxy method. The emission bands in UV range arising from the intrinsic radiative transition of Bi3+-based centers, and emission bands in visible range, related to luminescence of excitons localized around Bi-based centers, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…After doping the Bi 3+ ion, exciton localized around Bi 3+ ion is formed. Emission bands related to the exciton emission in YAG:Bi 3+ strongly overlaps with the 4f -5d 2 absorption bands of Ce 3+ ions peaked at 469 nm [19] . Therefore, the energy transfer from excitons to Ce 3+ results in enhanced absorption of Ce 3+ .…”
Section: (A) Nir Emission Intensities Versusmentioning
confidence: 84%
See 1 more Smart Citation
“…After doping the Bi 3+ ion, exciton localized around Bi 3+ ion is formed. Emission bands related to the exciton emission in YAG:Bi 3+ strongly overlaps with the 4f -5d 2 absorption bands of Ce 3+ ions peaked at 469 nm [19] . Therefore, the energy transfer from excitons to Ce 3+ results in enhanced absorption of Ce 3+ .…”
Section: (A) Nir Emission Intensities Versusmentioning
confidence: 84%
“…Several studies have also reported on the visible emission (477 nm) of Bi 3+ -doped YAG caused by the excitons localized near Bi 3+ ions [17,18] . The emission bands of Bi 3+ doping-induced excitons are strongly overlapped with the 4f -5d absorption bands of Ce 3+ ions with peak at 459 nm, thereby resulting in the efficient energy transfer from excitons to Ce 3+ ions in the YAG matrix [19] .…”
mentioning
confidence: 99%
“…Namely, an energy transfer from Bi 3+ to Ce 3+ might occur. It has been shown that Bi 3+ can be excited by UV, resulting in an emission band at around 486 nm, which is near the absorption band of Ce 3+ (460 nm). However, in this study, the excitation wavelength is in the visible range (460 nm), rather than in UV range.…”
Section: Resultsmentioning
confidence: 99%
“…Rare-earth aluminate garnets (Ln 3 Al 5 O 12 , LnAG), crystallizing in a bcc structure (space group: Ia-3d) with 160 atoms in the cubic cell [1], is a family of multi-functional ceramic materials, among which Lu 3 Al 5 O 12 (LuAG) has been extensively studied. Due to the unique 4f electron configuration of the rare earth elements, Ce 3+ activated LuAG is an important yellow phosphor that can be excited with blue light and thus is finding wide applications in white LED [2][3][4][5]. Eu 3+ and Tb 3+ doped LuAG are being considered as promising red and green phosphors, respectively, have been widely used in lighting and display areas [6].…”
Section: Introductionmentioning
confidence: 99%